2017
DOI: 10.1108/jfbm-02-2017-0006
|View full text |Cite
|
Sign up to set email alerts
|

Another hybrid? Family businesses as venture capitalists

Abstract: Purpose This paper addresses the phenomenon of venture capital firms which are also family businesses (VCFBs). The purpose of this paper is to explore and understand the phenomenon of VCFB by answering the following questions: What are the features of professionalization in VCFBs? And, how do professionalization and types of family businesses explain the strategies and governance of VCFBs? Design/methodology/approach As an explorative case study, it maps the Swedish venture capital (VC) industry and compares… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
26
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 7 publications
(26 citation statements)
references
References 64 publications
0
26
0
Order By: Relevance
“…Thus, the process of positioning is clearly related to the dynamic change of EO. Overall, this configuration highlights the individual level of EO (Nordqvist et al, 2008;Ljungkvist and Boers, 2017).…”
Section: Eo Configuration Developmentmentioning
confidence: 83%
See 2 more Smart Citations
“…Thus, the process of positioning is clearly related to the dynamic change of EO. Overall, this configuration highlights the individual level of EO (Nordqvist et al, 2008;Ljungkvist and Boers, 2017).…”
Section: Eo Configuration Developmentmentioning
confidence: 83%
“…Anderson et al, 2015). For example, the VC firm's management often works in close collaboration with the portfolio company's management (Ljungkvist and Boers, 2017;Bacon et al, 2013). Generally, VC firms often control the board and represent investors ( Jensen, 1993).…”
Section: Ownership Types and Eomentioning
confidence: 99%
See 1 more Smart Citation
“…The motives behind this increase are not fully understood, but some research has shown TFF owners' affinity towards certain external investors, such as individual investors, family offices (Neckebrouck et al, 2017) and investors that are family firms, i.e. VCFBs (Ljungkvist and Boers, 2017).…”
Section: Governance Practicesmentioning
confidence: 99%
“…Differences regarding governance and ownership are likely the most decisive elements distinguishing venture capital (VC) companies' goals and strategies (Bertoni et al, 2015). Since a significant proportion of VC companies are family-owned, their governance is affected by the generational changes in the owner family (Ljungkvist and Boers, 2017). However, more research on how the transgenerational aspect influence governance is needed (Suess, 2014;Suess-Reyes, 2017; which also concerns how different investor types handle the deal processes (Schickinger et al, 2018).…”
Section: Introductionmentioning
confidence: 99%